(3GdchcH GdOQi ajeG jJNQL Ydi GdCUhd GdfMhjI ef GdaQhY GdabgjIs - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG Cage ef GdHjGf hHYO , aEf Yde GdMdGd hGdMQGe GdPi Hg UdGM GdOfjG hGdCNQi hgh GdeSei HYde Gdabg eSJeO ef Yde CUhd Gdabg hYde GdYQHjI s
(3BNQgG (B:s
(3hgh hLg ENJGQg GdTjN ai GdKHfjI , hGdCUM Gfg dGTF ajg CUdkG , hGddg SHMGfg hJYGdi CYde Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3cJH GdYfGhjjf hHYV GdcdeGJ HGdMeQIs
(3Ydi ghGeTgG JUMjMGJ h JbjjOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs